Centella asiatica: from folk remedy to the medicinal biotechnology - a state revision - Alfarra, Helmi Yousif; Omar, Muhammad Nor (International Network for Natural Sciences, 2013)
Centella asiatica or “gotu kola” has been used since long time ago as an ethno-pharmacological plant and supposed to be a potent medicinal plant for its various pharmacological effects favorable for human health. Many studies described the noteworthy protective effect of C. asiatica against numerous diseases. Biological activities of C. asiatica have been linked to the most major compounds in it. This state paper is a part of our ongoing research on C. asiatica, its activity, isolation of novel metabolites, and applying the biotechnological methods to improve this plant and its phytochemical activities.